Case report: Rosai-Dorfman disease with rare extranodal lesions in the pelvis, heart, liver and skin - Yoshida, Misaki; Zoshima, Takeshi; Hara, Satoshi; Takahashi, Yoshinori; Nishioka, Ryo; Ito, Kiyoaki; Mizuhima, Ichiro; Inoue, Dai; Nakada, Satoko; Kawano, Mitsuhiro (Frontiers in Oncology, 2023)
Rosai-Dorfman disease (RDD), a rare form of non-Langerhans cell histiocytosis, can involve systemic extranodal lesions. Skin lesions are the most common, whereas intrapelvic, cardiac, and hepatic lesions are infrequent. The present study describes a 74-year-old woman with multiple extranodal lesions in the pelvis, heart, liver, and skin that were successfully treated with glucocorticoid therapy. She had experienced fever and persistent inflammation without cervical lymphadenopathy for several months and 18F-fluorodeoxyglucose (FDG) positron emission tomography (PET) showed abnormal FDG uptake in the left cheek; cervical, axillary, inguinal lymph nodes; periatrium; and pelvis. She was diagnosed with RDD based on skin and pelvic biopsies. Although this was an atypical case without bilateral cervical lymphadenopathy, the FDG-PET detection of inflammatory lesions led to selection of suitable biopsy sites, and pathological examination led to a correct diagnosis. Findings in this patient indicate that RDD can present with an atypical distribution of infrequent extranodal lesions, with attention required to prevent a delayed diagnosis.